The psychological distress and psychic phenomena in cancer patients during palliative care - Mukharovska, Inna (Psychosomatic Medicine and General Practice, 2016)
Background. Cancer diagnostics on incurable stages, the transition to palliative care because of disease progression are significant psychological challenges for the patient. Psychological help for cancer patients during palliative treatment is no less important than medical therapy. Methods. The study was conducted at the Kyiv City Clinical Cancer Center during the 2012 - 2013 years in two phases. In the first phase was provided a psychological investigation of incurable cancer patients and assessed its dynamics during palliative therapy with followed qualitative analysis of the data (n=436 patients). Second phase included determining factors of psychological maladjustment and evaluation intensity of mental distress – participated 63 palliative cancer patients. The SCL-90r used for assessment of psychic distress. Results. The prominent psychopathological symptoms in incurable cancer patients were somatization, depression and nonspecific symptoms. Less pronounced signs of mental distress in descending order of severity were anxiety, hostility, paranoid ideation, interpersonal sensitivity, obsessive-compulsive, psychoticism and phobic anxiety. Factors of psychological distress in cancer patients during palliative care include high physical distress; the impossibility of total control on physical and psychological symptoms; chronic pain; progressive deterioration of physical well-being; need to use opioids for relief pain; need for help; existential nature of stress; individual psychological characteristics. In patients identified psychological phenomena related to the palliative phase of treatment: psychological induction "pendulum", externalizing of mental stress, decentralization. Conclusions. Cancer patients in the palliative stage of treatment experiencing intensive psychological distress and clinically constitute a special group with specific psychological needs, which need to be considered in providing psychological care.